Can digital storytelling influence luxury brand perception? The case of Christian Dior - Rodrigues, Sofia Pinto (2022)
The research conducted in the context of this dissertation sought to study the influence of digital storytelling as a communication tool in consumers’ luxury brand perception of luxury brands. For this purpose, a case study of luxury brand Christian Dior was developed, through which digital stories produced and shared by the brand were analyzed and linked to its brand image among Portuguese consumers. For luxury brands, building their emotional appeal and symbolic value is crucial for their financial prosperity. More importantly, maintaining their luxury image, in the eyes of both luxury and non-luxury consumers, is considered fundamental. In turn, this aspirational and prestigious perception can be built from a unique brand identity, which needs to be properly communicated to the brands’ audiences. Hence, when a luxury brand makes the most out of storytelling’s capacity to educate consumers about a brand, communicate their identity, and kindle emotional connections, and symbolic brand value, by turning it into a piece of digital content, it becomes fair to question if it can influence consumers’ luxury perception of such brand. With the application of a mixed-methods approach, through a document analysis, qualitative content analysis, and survey, results show that, for the enquired Portuguese luxury and non-luxury consumers, digital storytelling had a persuasive effect, proving to have a positive influence on luxury brand perceptions of Dior for both sub-samples, although different dimensions of the concept were affected. The brand uses digital storytelling content in its digital campaigns to communicate its identity, engage with consumers emotionally, and showcase its aspirational and symbolic dimension, in order to build its high-end image. Results suggest that Dior could continue to use storytelling for the same branding purpose in future campaigns.